Comparison of changes in sugar contents in the cotyledons of Trigonella and Tamarindus - Gaikwad, Sweta; K, Sharma; Kanungo, V K (Recent Research in Science and Technology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]–> Fleshy cotyledons serve as the major storage organ in most non-endospermic legumes. Cotyledons serve as major storage organs with protein and carbohydrates as the major food reserves. Reserve food is broken down by the formation of various types of hydrolases (e.g., amylases, proteases, nucleases, lipases, etc.). In germinating seeds, the starch degraded for the formation of sugar, it was found that at the level of starch degradation, the accumulation of sugar in cotyledons of both Trigonella and Tamarindus was quite prominent. It was marked that sugar was the hydrolytic product of starch. It accumulated in the cotyledons along with the subsequent degradation of starch. In most of the cases it showed a decline in its level due to its translocation into the axis which acted as a link.